Inisiasi Kunjungan Postnatal Care Dengan Tingkat Kesakitan Fisik Pada Ibu Pasca Melahirkan - Ibrahim, Juliani; Annisa, Dhia Falih (Universitas Muhammadiyah Semarang, 2020)
Initiation of Postnatal Care Visits with Levels of Physical Pain in Postpartum MothersBackground: Postnatal services are a series of health services provided to mothers who have just given birth according to standars and performed at least three times according to the recommended schedule and implemented so far in primary, but the initiating of postnatal care visits is still low with what is expected and the high mortality and postpartum maternal morbidity is quite high in Indonesia due to vaginal infection and bleeding. Objective: To determined the relationship between postnatal care initiation and the of mother's postpartum physical illness using observational analytic research design with a cross-sectional approach. More than 81 respondents, they are postpartum mothers who had postnatal visits at least 3 months after giving birth.Method: Data collection by filling the checklist and interview. Then data were analyzed using the chi-square test. Result: As many as 69% of postpartum mothers who have birth spans of less than 2 years have the postpartum infection and as many as 71.6% of postpartum mothers who are late for a postnatal care initiation also have the postpartum infection. Conclusion: Less than 2 years of birth interval and late initiate of postnatal care visits are at risk of having a postpartum infection and are significantly associated with a high incidence of physicall ilness.